1995
DOI: 10.1016/0042-6989(94)e0049-q
|View full text |Cite
|
Sign up to set email alerts
|

Moving the retina: Choroidal modulation of refractive state

Abstract: The chick eye is able to change its refractive state by as much as 7 D by pushing the retina forward or pulling it back; this is effected by changes in the thickness of the choroid, the vascular tissue behind the retina and pigment epithelium. Chick eyes first made myopic by wearing diffusers and then permitted unrestricted vision developed choroids several times thicker than normal within days, thereby speeding recovery from deprivation myopia. Choroidal expansion does not occur when visual cues are reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
435
4
8

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(467 citation statements)
references
References 27 publications
16
435
4
8
Order By: Relevance
“…The rapid increase in choroidal thickness seen during recovery from form deprivation myopia was initially hypothesized to be a consequence of the choroid actively pushing the retina back toward the image plane of the highly myopic eye (29). Three speculations as to the source of choroidal expansion were offered: increased synthesis of extracellular matrix (i.e., proteoglycans) and͞or modulation of the nonvascular smooth muscle spanning the choroid, increased uveoscleral outflow, or choriocapillaris leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid increase in choroidal thickness seen during recovery from form deprivation myopia was initially hypothesized to be a consequence of the choroid actively pushing the retina back toward the image plane of the highly myopic eye (29). Three speculations as to the source of choroidal expansion were offered: increased synthesis of extracellular matrix (i.e., proteoglycans) and͞or modulation of the nonvascular smooth muscle spanning the choroid, increased uveoscleral outflow, or choriocapillaris leakage.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, it is known that ChT is affected by various factors such as blood pressure, age, gender, time of the day, refractive status, axial length, and forced hyperopic or myopic defocus. 2,[9][10][11] Further, a recent experimental study showed that anti-muscarinic agents could affect ChT. 12 Therefore, in the present study, we aimed to investigate the effects of tropicamide and cyclopentolate, which are two anti-muscarinic agents commonly used in the ophthalmologic practice, on subfoveal ChT measured by EDI OCT in healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…It has several functions including procurement of oxygen and nutrients for the outer retina, adjustment of retinal position, regulation of retinal temperature, protection of the photoreceptors, and secretion of some growth factors. 1,2 The introduction of enhanced depth imaging (EDI) optical coherence tomography (OCT) technology by Spaide et al 3 has provided accurate measurement of choroidal thickness (ChT) for investigating the in vivo anatomy of normal choroid and the choroidrelated ocular pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies show that the diurnal axial length rhythms are altered (magnitude increased) in form-deprived chicks (which stimulates excessive eye growth), resulting in myopia development (Weiss & Schaeffel, 1993;Wallman et al, 1995;Nickla et al, 1998b;Papastergiou et al, 1998). On the other hand, when chicks are exposed to myopic defocus (which slows/retards the eye growth), the diurnal axial length variations are found to be phase delayed, leading to a slowing of eye growth (Nickla et al, 1998b;Papastergiou et al, 1998;Nickla, 2006).…”
Section: Seasonal Variation In Longitudinal Axial Length Changes and mentioning
confidence: 99%
“…Studies with chicks show that the diurnal variations in choroidal thickness and axial length are altered in fast growing eyes of form-deprived chicks (Weiss & Schaeffel, 1993;Wallman et al, 1995;Nickla et al, 1998b;Papastergiou et al, 1998). During form-deprivation, the rhythms of axial length and choroidal thickness shift to an exact anti-phase relationship (i.e.…”
Section: Diurnal Ocular Variationsmentioning
confidence: 99%